Youth-adult partnerships: Examining the perceptions of youth and adult 4-H Foundation board members - Eric William Larsen (Montana State University, 2010)
The purpose of this study was to determine the effectiveness of youth adult partnerships within state 4-H foundation boards by assessing perceptions of youth and adult members toward one another. Evidence revealed that youth with prior youth-adult partnership experiences held less positive views regarding youth-adult partnerships than did the youth with no experience in a youth-adult partnership. Youth believed that adults were over-bearing and did not let the youth excel to their potential. Youth perceived adults were not actively listening to youth and were not taking youths' ideas seriously.